Metodologia para a representação de registro fotográfico de esculturas de arte sacra - Adriana Aparecida Lemos Torres (2019)
The photograph constitutes a type of iconographic document, that must be analyzed considering the author element (photographer) and the documental (information source) components. So, it can perform different functions; such as in the field of arts, the photograph can act as a work or as a record of a work. At the memory institutions, it holds a documental role and contributes to the register of a domain. The religious art photography keeps information about the portrayed work available, allowing their disclosure and the dissemination of the History and Culture. The photography collections in either physical or virtual repositories require organization and representation for the relevant content to be highlighted, and aligned to the repository's purpose, enabling a more efficient information retrieval. Lately, some researches have been proposing specific methodologies for the representation of photographies, since these ones have attributes that are distinct from the verbal text record ones. Although, there wasn’t found any methodology that was able to encompass all of the aspects that are considered relevant to the representation of photographies of religious art sculptures on the literature, when taking into account the biographical and visual aspects to the interpretative and symbolic ones. As a result of this lack, the general objective of this research proposes a methodology for the representation of iconographic documents of the photograph type, especially of religious art sculptures, in order to allow the treatment of this type of documents, aiming the recovery of information contained in them, based on their intrinsic and extrinsic aspects, and taking into consideration the attributes of the work portrayed in the photograph. The theoretical basis for the construction of this unified methodology included the specialized literature methodologies that cover thematic and descriptive representation about photographs as part of the Historical and Cultural Heritage, the iconographic document, history, characteristics and attributes of photographs, and some metadata patterns of image representation. For the development of this proposal, there were examined the methodologies related to the representation of photographic records that could meet the specificities of the photographs of sacred art sculptures, considering the methods of different authors (PANOFSKY, 1979; BLÉRY, 1981; SHATFORD LAYNE, 1986; SMIT, 1996; ALVES, VALERIO, 1998; MANINI, 2002). Based on the literature review, it was verified that both methodologies focus on thematic and descriptive representation. In general, the methodologies don’t null each other out, some of them overlap each other, and others yet, are complementary, to a certain extent, to benefit a wider representation. For the validation of the proposed methodology, four religious art sacred images were used as a sample from two collections: an artist photographic collection and a photographic collection of a specialist in History of Art. The obtained analysis of the results presented indicate that the thematic representation elements must be complemented by the descriptive representation elements, since they can be considered relevant access points for an efficient information retrieval. One of the contributions of this research is to emphasize that sharing religious art information can be a way to return to the society the heritage, cultural and historical legacies that belong to them. Specifically, for the Information Science area, the unified methodology proposal shown in this study can satisfy different and real information representation demands from both physical and virtual image collections. Finally, for the Architecture Knowledge Organization research area, this work enables an advancement on the construction of knowledge about the representation of iconographic documents.